Your Brain on Google: Patterns of Cerebral Activation during Internet Searching - Small, Gary W.; Moody, Teena D.; Siddarth, Prabha; Bookheimer, Susan Y. (The American journal of geriatric psychiatry, 2009)
Previous research suggests that engaging in mentally stimulating tasks may improve brain health and cognitive abilities. Using computer search engines to find information on the Internet has become a frequent daily activity of people at any age, including middle-aged and older adults. As a preliminary means of exploring the possible influence of Internet experience on brain activation patterns, the authors performed functional magnetic resonance imaging (MRI) of the brain in older persons during search engine use and explored whether prior search engine experience was associated with the pattern of brain activation during Internet use. Cross-sectional, exploratory observational study The authors studied 24 subjects (age, 55–76 years) who were neurologically normal, of whom 12 had minimal Internet search engine experience (Net Naive group) and 12 had more extensive experience (Net Savvy group). The mean age and level of education were similar in the two groups. Patterns of brain activation during functional MRI scanning were determined while subjects performed a novel Internet search task, or a control task of reading text on a computer screen formatted to simulate the prototypic layout of a printed book, where the content was matched in all respects, in comparison with a nontext control task. The text reading task activated brain regions controlling language, reading, memory, and visual abilities, including left inferior frontal, temporal, posterior cingulate, parietal, and occipital regions, and both the magnitude and the extent of brain activation were similar in the Net Naive and Net Savvy groups. During the Internet search task, the Net Naive group showed an activation pattern similar to that of their text reading task, whereas the Net Savvy group demonstrated significant increases in signal intensity in additional regions controlling decision making, complex reasoning, and vision, including the frontal pole, anterior temporal region, anterior and posterior cingulate, and hippocampus. Internet searching was associated with a more than twofold increase in the extent of activation in the major regional clusters in the Net Savvy group compared with the Net Naive group (21,782 versus 8,646 total activated voxels). Although the present findings must be interpreted cautiously in light of the exploratory design of this study, they suggest that Internet searching may engage a greater extent of neural circuitry not activated while reading text pages but only in people with prior computer and Internet search experience. These observations suggest that in middle-aged and older adults, prior experience with Internet searching may alter the brain's responsiveness in neural circuits controlling decision making and complex reasoning.